Does ESG performance enhance investment efficiency? A study of Chinese firms with auditing quality as a mediator - Jamal, Surayya; Imran, Asma; Mustafa, Kiran; Faraz, Ansar Ali; Rehman, Shafiq Ur (The Economics and Finance Letters, 2026)
Growing demands for non-financial information have increased the importance of environmental, social, and governance (ESG) disclosures in corporate decision-making. This study examines whether ESG performance improves investment efficiency in Chinese A-share listed firms and investigates whether audit quality mediates this relationship. Using a panel dataset of Chinese A-share firms from 2012 to 2023, ESG performance is measured using Bloomberg ESG pillar scores, while investment efficiency is estimated based on deviations from optimal investment levels. Firm-level fixed-effects regression models are employed to control for unobserved heterogeneity, and mediation analysis is applied to assess the indirect effect of audit quality. The empirical results indicate that ESG performance has a significant and positive effect on investment efficiency. A one-unit increase in ESG score is associated with an improvement of approximately 0.027 in investment efficiency at the 1% significance level. Audit quality, proxied by engagement with Big-4 auditors, is also positively associated with investment efficiency, with an estimated effect of about 0.006. Mediation analysis confirms that audit quality partially transmits the influence of ESG performance on investment efficiency, suggesting that high-quality auditing enhances the credibility of ESG disclosures and strengthens their role in guiding efficient investment decisions. These findings have important practical implications. Firms can improve investment efficiency by strengthening ESG practices and engaging high-quality auditors. Policymakers and regulators may enhance capital allocation efficiency by promoting standardized ESG disclosure requirements and improving audit oversight.